2020
DOI: 10.1002/jia2.25590
|View full text |Cite
|
Sign up to set email alerts
|

Acute and early HIV infection screening among men who have sex with men, a systematic review and meta‐analysis

Abstract: Introduction: Screening for acute and early HIV infections (AEHI) among men who have sex with men (MSM) remains uncommon in sub-Saharan Africa (SSA). Yet, undiagnosed AEHI among MSM and subsequent failure to link to care are important drivers of the HIV epidemic. We conducted a systematic review and meta-analysis of AEHI yield among MSM mobilized for AEHI testing; and assessed which risk factors and/or symptoms could increase AEHI yield in MSM. Methods: We systematically searched four databases from their ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…Our data suggest that if a more stringent cutoff of the behavioral or symptom score would be used to select people for HIV RNA testing, the AEHI yield could be up to 3.7% (behavioral score) or 20.0% (symptom score), while only offering HIV RNA testing to a small subset of participants. This is consistent with findings from our recently conducted meta-analysis, in which the pooled estimate for AEHI screening targeted to behaviorally vulnerable or symptomatic GBMSM was 11.1% (95% CI, 5.9%–17.6%) [ 18 ]. However, using a higher cutoff will inevitably miss a substantial proportion of AEHI cases and should only be used when resources are constrained.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data suggest that if a more stringent cutoff of the behavioral or symptom score would be used to select people for HIV RNA testing, the AEHI yield could be up to 3.7% (behavioral score) or 20.0% (symptom score), while only offering HIV RNA testing to a small subset of participants. This is consistent with findings from our recently conducted meta-analysis, in which the pooled estimate for AEHI screening targeted to behaviorally vulnerable or symptomatic GBMSM was 11.1% (95% CI, 5.9%–17.6%) [ 18 ]. However, using a higher cutoff will inevitably miss a substantial proportion of AEHI cases and should only be used when resources are constrained.…”
Section: Discussionsupporting
confidence: 91%
“…We recently conducted a systematic review and meta-analysis of studies reporting strategies to mobilize GBMSM for AEHI testing [ 18 ]. We found that targeted AEHI testing (ie, testing of individuals with certain behavioral factors or symptoms) resulted in substantially higher AEHI yields than universal AEHI testing, and that AEHI yield may be increased by using published behavioral and/or symptom scores [ 19–21 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings concur with others in suggesting such approaches alone have unacceptably poor diagnostic performance 37,38 . The decreasing complexity and cost of point-of-care PCR technologies should encourage policy makers to re-evaluate the cost effectiveness of providing access to PCR-based HIV and STI diagnostics particularly in community settings 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Palmer et al . [45] conducted a systematic review and meta‐analysis of studies reporting strategies of mobilising MSM for testing to identify acute and early HIV infection (AEHI) and their yield of AEHI cases. Overall, AEHI was identified in 6.3% (95% CI: 2.1 to 12.4) and acute HIV infection in 0.7% (95% CI: 0.4 to 1.2) of the visits at which it was assessed.…”
Section: The Hiv Prevention and Care Cascade: Innovative Engagements mentioning
confidence: 99%